Teacher Strategies in Realizing the Pancasila Student Profile Through Mathematics Learning in Elementary Schools - Gayo, Adhila Irma Prianti (Program Magister Teknologi Pendidikan Universitas Jambi, 2018)
This research aims to describe the strategies used by teachers in developing Pancasila student profiles through mathematics learning at the elementary school level. This research adopts a qualitative approach with a focus on the phenomenological to describe teachers' strategies in creating Pancasila student profiles through mathematics learning. Research data was collected through interviews with class I E teachers as the main source, as well as through participatory observation and documentation as additional data sources. The research results showed that class I E teachers implemented various strategies to achieve this goal. First, in creating a profile of students who are believers, devoted to God Almighty, and have noble character, teachers become role models for students in practicing religious values and taking a personal approach to students. Second, to develop a globally diverse profile of students, teachers provide an understanding of various cultures in Indonesia. Third, to encourage the profile of students working together, teachers organize group activities and teach the values of cooperation and sincerity. Fourth, to develop an independent student profile, teachers provide individually challenging assignments and provide extra challenges to complete. Fifth, in developing the profile of students who think critically, teachers use group division to encourage students to explore information, evaluate, analyze and make conclusions. Teachers also act as motivators for students. Finally, to develop creative student profiles, teachers create fun learning, interact with students to develop their creativity, and connect learning with the context of everyday life. As a facilitator, the teacher supports the student's learning process.